2016
DOI: 10.5614/j.math.fund.sci.2016.48.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Interannual Modulation of Intraseasonal Kelvin Waves in the Equatorial Indian Ocean

Abstract: Abstract.Outputs from a high-resolution ocean general circulation model (OGCM) for the period of 1990-2003 indicate an interannual modulation of intraseasonal Kelvin waves along the equatorial Indian Ocean. During normal conditions without IOD event, the first mode explains about 30-40% of the total variance in the western (60-65ºE) and central (75-80ºE) basin, while the second mode contributes up to 45% to the total variance in the central basin around the longitude of 82ºE. In contrast, during the 1997/98 IO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…They did not analyze the influence of SMC on the ISV of the SBOB's currents during summer 2016. Previous studies have shown that the IOD events can modulate the ISV of southeastern tropical Indian Ocean by altering the baroclinic instability of the SEC/ITF system (Ogata & Masumoto, 2010, 2011) and by changing the oceanic stratification structure in the equatorial Indian Ocean to affect the contribution of higher‐order baroclinic modes (Iskandar et al., 2016; Qiu et al., 2012). Strong exchange of matter and energy between SBOB and equatorial Indian Ocean has a great impact on the ISV of the upper ocean currents.…”
Section: Introductionmentioning
confidence: 99%
“…They did not analyze the influence of SMC on the ISV of the SBOB's currents during summer 2016. Previous studies have shown that the IOD events can modulate the ISV of southeastern tropical Indian Ocean by altering the baroclinic instability of the SEC/ITF system (Ogata & Masumoto, 2010, 2011) and by changing the oceanic stratification structure in the equatorial Indian Ocean to affect the contribution of higher‐order baroclinic modes (Iskandar et al., 2016; Qiu et al., 2012). Strong exchange of matter and energy between SBOB and equatorial Indian Ocean has a great impact on the ISV of the upper ocean currents.…”
Section: Introductionmentioning
confidence: 99%